2022
DOI: 10.1186/s13045-022-01255-x
|View full text |Cite
|
Sign up to set email alerts
|

Rewiring mitochondrial metabolism to counteract exhaustion of CAR-T cells

Abstract: Short persistence and early exhaustion of T cells are major limits to the efficacy and broad application of immunotherapy. Exhausted T and chimeric antigen receptor (CAR)-T cells upregulate expression of genes associated with terminated T cell differentiation, aerobic glycolysis and apoptosis. Among cell exhaustion characteristics, impaired mitochondrial function and dynamics are considered hallmarks. Here, we review the mitochondrial characteristics of exhausted T cells and particularly discuss different aspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 175 publications
0
26
0
Order By: Relevance
“…However, it has been reported that the chloroplast genomes provided insufficient phylogenetic information to distinguish between closely related sugarcane cultivars, due to the cultivars’ recent origin and the genome conserved sequences ( Evans et al, 2019 ). In contrast, the mitochondrial genomes (mitogenome) of plants are larger ( Sloan et al, 2012 ), more plastic ( Turnel et al, 2003 ; Rubinstein et al, 2013 ; Huang et al, 2022 ), and may contain increased phylogenetic signals ( Duminil and Besnard, 2021 ). For instance, one of the main advantages of the mitogenome as a phylogenetic marker stem from the fact that its 36 genes have different rates of substitution, with some having higher rates than others, allowing relatively recent divisions to be tracked, and those having slower rates of substitution, deemed useful for elucidating deeper relationships ( Saccone et al, 1999 ; Cho et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, it has been reported that the chloroplast genomes provided insufficient phylogenetic information to distinguish between closely related sugarcane cultivars, due to the cultivars’ recent origin and the genome conserved sequences ( Evans et al, 2019 ). In contrast, the mitochondrial genomes (mitogenome) of plants are larger ( Sloan et al, 2012 ), more plastic ( Turnel et al, 2003 ; Rubinstein et al, 2013 ; Huang et al, 2022 ), and may contain increased phylogenetic signals ( Duminil and Besnard, 2021 ). For instance, one of the main advantages of the mitogenome as a phylogenetic marker stem from the fact that its 36 genes have different rates of substitution, with some having higher rates than others, allowing relatively recent divisions to be tracked, and those having slower rates of substitution, deemed useful for elucidating deeper relationships ( Saccone et al, 1999 ; Cho et al, 2004 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is thus reasonable to postulate that perturbations to either the BM or the thymic microenvironment may affect the other and be at least partly responsible for the observed immunosenescence in patients with AML. The intense interest and scrutiny of T-cell based immunotherapies in hematological malignancies lends impetus to developing novel strategies to overcome T cell immune dysfunction in vivo ( 293 ). The clinical features of CAR-T cell exhaustion in vivo have been investigated by studying cell proliferation, cytotoxicity, and the median persistence of CAR-T cells in peripheral blood, which was found to be within a range of 20 to 617 days ( 294 ).…”
Section: Discussionmentioning
confidence: 99%
“…Second and third generation CAR T cells have incorporated one or two costimulatory signals, respectively. Genetic modifications to CARs for co-expression of cytokine ( 92 98 ), chemokine ( 99 101 ), or both factors ( 102 104 ) have been successfully used to enhance therapeutic efficacy CAR T cells.…”
Section: Brief Overview Of Car T Cell Manufacture Process and The Ass...mentioning
confidence: 99%